The effects of size and habitat on δ N-15 of carnivorous plants (Drosera spp.) - Mgidi, Theresa Nobuhle (Department of Biological Sciences, 2017)
The δ N-15 natural abundance method was used to investigate the role of nutrient-poor habitats in carnivorous Drosera capensis and Drosera aliciae, and how that role changes under sunny and shady environmental conditions. The main purpose of the study was to evaluate Givnish's (1984) cost/benefit model used to explain the evolution of carnivory in nutrient-poor, sunny and moist habitats. δ N-15and total nitrogen values of the Drosera species were compared against each other, as well as against the non-carnivorous reference plants collected from each of the two habitats. Generally, data indicated significant differences between the carnivorous plants and their reference plants in terms of δ N-15 values. However, there was no significant difference between plants collected from the shade and those collected from the sun for both Drosera species. Total nitrogen results revealed higher values for Drosera plants from Camp's Bay than those from Table Mountain did. This indicated that there was a bigger source of insect nitrogen at that site, meaning more insects were available and being caught by the plants at Camp's Bay. Further investigations were performed on the two Drosera species in order to find the influence of altitude, leaf-size and plant form, on the degree of carnivory. There was an overall, higher degree of carnivory at Camp's Bay where it is, seasonally wet and the plants have longer leaves and a stem-like rosette. On Table Mountain it is cooler, waterlogged, and the plants have short leaves and ground-level rosettes therefore, the degree of carnivory there was lower. Lastly, chlorophyll and anthocyanin contents were measured and compared between the sun and shade collected D. capensis plants, with tentacles intact and with them removed. Chlorophyll investigations showed significant differences between sun and shade collected D. capensis plants but these were not affected by the removal of tentacles. Alternatively, anthocyanin measurements indicated that sun and shade collected D. capensis plants have similar amounts of anthocyanins, but the removal of tentacles results in a decrease (about four times lower) in the anthocyanin content.